Methylation and Expression of Retinoblastoma and Transforming Growth Factor-β1 Genes in Epstein-Barr Virus-Associated and -Negative Gastric Carcinomas - Xia Liu; Xiuming Tang; Shaoyan Zhang; Yun Wang; Xiaofeng Wang; Chengquan Zhao; Bing Luo (Gastroenterology Research and Practice)
Background. Retinoblastoma (RB) and transforming growth factor-β1 (TGF-β1) are important tumor-related factors. Methods. A series of 30 EBV-associated gastric carcinoma (EBVaGC) and 38 matched EBV-negative gastric carcinoma (EBVnGC) tissues were examined for the promoter methylation of RB by methylation-specific PCR (MSP) method. The expression of RB and TGF-β1 in gastric carcinoma tissues was detected by immunohistochemistry. Results. The methylation rate of RB gene in EBVaGC and EBVnGC was 80.0% (24/30) and 50.0% (19/38), respectively. The difference of RB methylation rate between EBVaGC and EBVnGC was significant (χ2=6.490,  P=0.011). There was no significant difference for RB expression between EBVaGC (43.3%, 13/30) and EBVnGC (63.2%, 24/38), and also for TGF-β1 between EBVaGC (56.7%, 17/30) and EBVnGC (63.2%, 24/38). RB methylation was not reversely correlated with RB expression in gastric carcinoma tissues (χ2=2.943,  P=0.086,  r=0.208). RB methylation, loss expression of RB, and TGF-β1 expression were significantly associated with tumor invasion and lymph node metastasis (P<0.05), but was not associated with sex, age, histological subtype (differentiation status) and tumor location. Conclusions. Methylation of RB is a common event in gastric carcinomas and EBV induces methylation of RB in EBVaGC, which may contribute to the development of gastric carcinomas. EBV has no significant effect on induction of TGF-β1 expression. Detection of RB methylation, RB expression, and TGF-β1 expression may be helpful to judge the status of tumor invasion and lymph node metastasis in gastric carcinomas.